On the Stress Distrubution in Bending of Strongly Anisotropic Beams - Blinowski, A.; Ostrowska-Maciejewska, J. (Engineering Transactions, 1995)
The displacement function method for the plane problems of linearly elastic orthotropic bodies has been proposed. The method has been used for the estimation of the rate of decay of the end effects in beams and slabs subjected to bending; the results obtained turned out to be in agreement with the earlier estimates obtained by Choi and Horgan for the influence of the end effects in the case of laboratory test specimens. Some possibilities of obtaining the rigorous solutions modeling special cases of bending have been shown. A set of explicit formulae has been proposed for the approximate solutions of bending problems taking into account the end effects, normal stress nonlinear distribution at the cross-sections and the contribution of the shear deformation to the beam deflection.